Wilfred Own Re-Visited: A Psychoanalytic Reading of War, Memory, and Crisis of Identity in Wilfred Owen’s Poem Mental Cases - Güneş, Ali (Journal of History Culture and Art Research, 2017)
This paper focuses upon the psychoanalytic reading of Wilfred Owen’s poem Mental Cases. In so doing, first, the paper examines how the disturbing experiences and feelings of a tragic event such as a war, torture, rape or murder, which the surviving victims, civilians and veteran soldiers store in the realm of their unconscious in the Freudian sense, start annoying their feelings after a while. That is, these memories of the past event continuously come later on in life under the troubling influence of recurring flashbacks of the traumatic events, nightmares, irritability, anxiety, and social withdrawal. Eventually these undesirable traumatic past experiences and memories repressed in the unconscious obviously causes individuals to have a kind of psychological disorder which powerfully affects their daily behaviour, life and identity. Secondly, the paper explores this relationship between conscious and unconscious aspect of life, along with the perception of identity, in Owen’s poem Mental Cases, in which the shell-shocked, war-torn veteran soldiers, who experienced and witnessed the shock of World War I and the death of their fellow soldiers, constantly remember the soldiers and innocent civilians who were brutally killed or whom they brutally killed in World War I. Now, these veteran soldiers call back those unhappy times, along with the death of soldiers and civilians, and then suffer in their psyche with a sense of guilt and disappointment: that is, recalling their shocking traumatic war experiences and their killing of many innocent people apparently cripple their vision of life and shatter their identities in the present. Through his representation of these veteran soldiers in such a way, Owen, as in his other poems, artistically and forcefully shows his own reaction, anger and dissatisfaction about the war and its distressing outcome in Mental Cases. Finally, the paper also examines how Owen’s critical view of war and its traumatic post-war effect still find meaning today because we unfortunately witness every day the loss of millions of lives in the contemporary world. As the post-effect, the paper will give from the Bosnian civil war during the period of 1992-1995.